Effect of aqueous dilution on the absorption of the nerve agent VX through skin in vitro. (December 2018) - Dalton, Christopher; Graham, Stuart; Jenner, John
Abstract: The in vitro percutaneous penetration of the nerve agent VX through pig skin was measured in the absence and presence of water or artificial sweat to determine the impact such conditions might have on penetration rates. Experiments were performed with Franz-type glass diffusion cells containing dermatomed pig skin as a surrogate for human skin. The receptor fluid used was 50% aqueous ethanol. 14 C labelled VX was applied to the skin surface under infinite or finite dosing conditions with regular receptor fluid sampling up to 24 h. Penetration from aqueous solutions of VX showed the maximal steady state penetration rate (Jss) was from the 50% (v:v) solution (366 ± 149 μg·cm −2 ·h −1 ), this being ~2.2 fold greater than Jss measured for neat VX (169 ± 89 μg·cm −2 ·h −1 ). Application of neat VX to water-wetted skin was also found to result in an increased penetration rate, compared to dry skin, shortly after contamination. These studies have shown that, in vitro, aqueous solutions of VX in contact with the skin can result in increased penetration rates when compared to neat VX applied to dry skin. Highlights: Measurement of VX percutaneous penetration in presence of water or artificial sweat VX in 50% aqueous solution had increased penetration compared to neat VX. The penetration rate of VX may be increased shortly after it contaminates wet skin. Presence of water may alter VX diffusion by changing the permeability coefficient.